Functional Interaction of Monoubiquitinated FANCD2 and BRCA2/FANCD1 in Chromatin - Wang, XiaoZhe (American Society for Microbiology, 2004)
Fanconi anemia (FA) is an autosomal recessive cancer susceptibility syndrome with at least 11 complementation groups (A, B, C, D1, D2, E, F, G, I, J, and L), and eight FA genes have been cloned. The FANCD1 gene is identical to the breast cancer susceptibility gene, BRCA2. The FA proteins cooperate in a common pathway, but the function of BRCA2/FANCD1 in this pathway remains unknown. Here we show that monoubiquitination of FANCD2, which is activated by DNA damage, is required for targeting of FANCD2 to chromatin, where it interacts with BRCA2. FANCD2-Ub then promotes BRCA2 loading into a chromatin complex. FANCD2(−/−) cells are deficient in the assembly of DNA damage-inducible BRCA2 foci and in chromatin loading of BRCA2. Functional complementation with the FANCD2 cDNA restores BRCA2 foci and its chromatin loading following DNA damage. BRCA2(−/−) cells expressing a carboxy-terminal truncated BRCA2 protein form IR-inducible BRCA2 and FANCD2 foci, but these foci fail to colocalize. Functional complementation of these cells with wild-type BRCA2 restores the interaction of BRCA2 and FANCD2. The C terminus of BRCA2 is therefore required for the functional interaction of BRCA2 and FANCD2 in chromatin. Taken together, our results demonstrate that monoubiquitination of FANCD2, which is regulated by the FA pathway, promotes BRCA2 loading into chromatin complexes. These complexes appear to be required for normal homology-directed DNA repair.